Bad Bunny : global takeover [videorecording (DVD)] - Randall, Nick; Bad Bunny, 1994-; Weeknd, 1990-; General (Rapper) (MVD Visual, 2026)
Bad Bunny, known as the 'King of Latin Trap,' brought reggaeton music to the global stage, following artists like Daddy Yankee. Not many music artists can claim to be a famous pop star, professional wrestler, and activist - meet the 'King of Latin Trap,' Bad Bunny. Bad Bunny is known for bringing reggaeton music onto the global stage. Dive into it₂s Caribbean roots of Reggaeton with artists like El General, Ivy Queen, Daddy Yankee and Karol G.